SILASE ISI RUMEN SEBAGAI PAKAN PENGGANTI HIJAUAN JAGUNG TERHADAP PRODUKSI SUSU SAPI PERAH PERANAKAN FRIESIAN HOLSTEIN - , Isnandar, Ir.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted in terms of determining the nutrient value of silage rumen content, and influencing the substitute of corn forage basal feeding on the productivity and quality of milk Holstein Friesian dairy cattle. There are three main researches summarized in this dissertation. This research reviewed the optimization of the Study of Lactic Acid Bacteria (LAB), in which the silage fermentation process was in the rumen contents that were gained from the slaughter house. In terms of producing 35% dried matter, it was combined with the dried cassava. The treatment given was by increasing the molasses additive materials. They were 0% (m0), 4% (m4), and 8% (m8) and LAB acidophilus inoculation (ac), LAB casei (ca),LAB plantarum (pl), LAB mixture (bm), LAB rumen (br), and without LAB inoculation (b0). The measuring done to the variables was after the silage had passed the 21 days of ensilaging. It included the measuring of pH, the content of lactic acid, acetic acid, butyric acid, N-NH3, dried matter, organic matter, crude protein, crude fiber, nitrogen free extracted, a number of bacteria, and organoleptic silage. The second research discussed the ensilage duration effect of the dominant result of the three LAB homofermentativeinoculation in the first research. Based on this research, there were two factors included in this research, they were the duration factor of ensilaging during 1 week (1 st week), 2 weeks (2 nd week), 3 weeks (3 rd week), and 4 weeks (4 th week). The second factor was inoculation of LAB plantarum, the blending LAB (bm), and the rumen contentLAB (br). The variables measured were pH, the content of lactic acid, acetic acid, butyric acid, N-NH3, the dry matter (DM), the organic matter (OM), the crude protein (CP), the crude fiber (CF), the nitrogen free extracted (NFE), the amount of lactic acid bacteria and the silage of organoleptic. The first and second statistical analyses were done by using ANOVA. The significant difference result was analyzed by using Duncanâs multiple range tests. The third phase of the study was in vivo testing using 16 cows in the second and third periods of lactation. Furthermore, this phase was divided into 4 treatment groups namely100% corn forage basal feeding and 0% silage (R1), 67% corn forage and 33% silage (R2), 33% corn forage and 33% silage (R3), and 0% corn forage and 100% silage (R4). Each of the feeding treatment used 4 cows consisting of four magnitude classifications of body weight. Each cow was treated by using corn forage basal feeding or silage and added 1 kg concentrate for 2 liters milk produced in a day. The variables measured included the dry matter digestibility (DMD), the organic matter digestibility (OMD), the crude protein digestibility (CPD), the dry matter intake (DMI), the organic matter intake (OMI), the crude protein intake (CPI), the total digestible nutrients (TDN), the milk produced in a day, the fat milk content, the protein milk, the milk specific gravity, the total solid (TS), the solid non fat (SNF) and the degree of milk acidity by Soxhlet Henkel. The data collected was analyzed by using variance analysis of latin square. If there was any difference among the treatment, the variables would be analyzed by using Duncanâs multiple range test. In the first research obtained the result of silage with pH around 3.79 - 4.49 from the treatment of br.m8 and b0.m0, the content of lactic acid was around 2.41% - 6.27% from the treatment of b0.m0 and pl.m8, the acetic acid was .64% - 1.68% from the treatment of pl.m8 and b0.m0, the butyric acid was .08% - .51% from the treatment of br.m8 and b0.m0, the N-NH3 was 2.67% - 6.52% from the treatment of pl.m8 and b0.m0, the organoleptic value was 57.18 - 86.07 from the treatment ofb0.m0 and pl.m8, the decreasing content of the dried matter was 4.41% - 10.26% from the treatment ofpl.m8 and b0.m0,the decreasing content of organic matter was 6.00% - 11.01%from the treatment ofpl.m8 and b0.m0, the decreasing content of CP was 1.80% - 9.75%from the treatment ofpl.m8 and b0.m0, the decreasing content of NFE was 3.61% - 6.79%from the treatment ofpl.m8 and b0.m0, the increasing content of crude fiber was 1.08% - 4.69% from the treatment ofpl.m8 and b0.m0, the development amount of LAB was around 1.2X107â 6.2X108from the treatment ofb0.m0 and pl.m8. The result of research I showed the treatment of using the LAB plantarum inoculants, the blending inoculants, LAB from the rumen content, and the adding of molasses additive consecutive 8% produced the lactic acid content silage of 6.27%, 5.73%, and 5.16% and the amount of LAB were 6.2X108, 5.7X108, and 5.1X108 they were higher than pH 3.84, 3.84 and 3.79, the content of acetic acid were .64%, 1.05% and .86%, the content of butyric acid were .09%, .14%, and 0,08%, ammonia were 2.67%, 2.97% and 2.98%, which were lower than the previous one. The average of the decreasing of the DM were 4.41%, 5.25%, and 6.04%, the decreasing of CP were 6.00%, 6.27%, and 6.45%, organic matter 1.80%, 1.95%, and 4.17%, which were lower than the treatment of using LAB acidophilus inoculants, LAB casei inoculants, and without LAB inoculants (b0).The second research showed the using of inoculants of LAB plantarum, the blending LAB, the LAB from the rumen content, and the adding of molasses additive 8% produced silage, in which the average of lactic acid were 4.70%, 3.88% and 3.46%, and the amount of the LAB were 3.40X108, 2.94X108, and 2.70X108. The pH degrees of silage acidity were 4.07, 4.13, and 4.44, the acetic acid contents were .45%, .71%, and .84%, the butyric acid contents were .05%, .07%, and .10%, the contents of ammonia were 1.85%, 2.08%, and 2.42%, the decreasing contents of DM were 4.49%, 5.00%, and 5.04%, the decreasing contents of organic matter were 2.45%, 2.61%, and 2.79%, the increasing contents of CP were 1.69%, 2.15%, and 4.44%, the decreasing of crude fiber contents were 3.37%, 3.46%, and 3.65%, the values of organoleptic were 59.01, 58.75, and 58.75. Each of them was based on the treatment of using LAB plantarum, the blending LAB, and LAB from the rumen content. The role of ensilage duration showed the using of LAB plantarum inoculants produced a better silage than the using of blending LAB and LAB from the rumen content. They were showed by the reaching of pH silage, which were 4.05, 4.35, and 4.33 on the second week, while the contents of lactic acid were 5.19% / DM, 4.76% / DM, and 4.01% / DM. The ensilage duration affects to the lactic acid fermentation, the fastest fermentation was reached on the second week (at the 8 th days â 14 th ), which was followed by the third week (at the 15 th days â 21 st ), then the first week (at the 1 st day â 7 th ) and the fourth week (at the 22 nd days â 28 th ), with the lactic acid contents were 4.65%, 5.38%,0,58%, and 5.43%.The third research showed the consumptions of the rumen content silage a day as the basal feeding for lactating dairy cattle, which were 13.54 kg of DM, 10.39 kg of OM, 10.38 kg of TDN, 1499 g of CP for the R4 treatment (100% silage)